A rare case of early-onset neonatal sepsis caused by Proteus mirabilis in the first infant of tetrachorionic triamniotic triplets - A. L. Karpova; A. V. Mostovoi; O. V. Avdei; E. A. Dudkina; S. P. Zagdai; L. A. Anikeeva; A. P. Khoteeva; O. E. Orlova; N. Yu. Karpov (Акушерство, гинекология и репродукция, 2024)
Early-onset neonatal sepsis (EОNS) is one of the most severe diseases of the neonatal period and is often coupled to extremely unfavorable outcomes. In many ways, the severity of the condition and the results of newborn nursing depend on the etiology of the bacterial process. The major EОNS pathogens are traditionally considered to be Streptococcus group B and E. coli, much less common are other Gram-negative bacteria including casuistic cases caused by caused by Proteus mirabilis (P. mirabilis). The article provides a review on the P. mirabilis role in developing neonatal sepsis with pathogen-specific disease course and outcomes. In addition, we describe a clinical case of P. mirabilis-caused EОNS not only primarily characterized by the rarity of its causative agent, but also that it proceeded with a more favorable brain damage in contrast to similar cases described worldwide and because the neonatal EОNS developed in one of triplets, with two other babies being asymptomatic despite that P. mirabilis was also detected.